Meningkatkan Keindahan Arsitektural Jembatan Surya Lembayung Kebun Raya Bogor dengan Tanaman Lanskap - SYAHADAT, RAY MARCH; PUTRA, PRIAMBUDI TRIE; PATIH, TANDRI (Jurnal Arsitektur Lansekap; Vol.3, No.1, April 2017, 2017)
ABSTRACT Improving the Architectural Beauty of Surya Lembayung Bridge at Bogor Botanical Gardens with Landscape Plant Surya Lembayung Bridge is one of bridge in the Bogor Botanical Gardens. Unlike the iconic bridges in the Bogor Botanical Gardens, the Surya Lembayung Bridge looks plain. Actually, the visual quality of the bridge can be increased with the addition of plants on either side of the bridge bodies. Therefore the visual quality needs to be assessed with a perceptional approach. The methods that used on this article were scenic beauty estimation, semantic differential, factor analysis, and multidimensional scaling. The results showed that the addition of plants in generally can improve the visual quality of the bridge. The highest visual quality is the bridge with the addition of Zephyranthes grandiflora. Keywords: perception, scenic beauty estimation, multidimensional scaling, visual quality, Zephyranthes grandiflora